An Analysis of the Teachers’ Strategies in Teaching English Vocabulary at the Seventh Grade of Mts N 7 Kebumen in the Academic Year 2019/2020 - Garwan, Hellaisna Nur'Aini; Priyanti, Henny (English Education and Literature Journal (E-Jou), 2021)
Teaching vocabulary is one way to increase students' knowledge so they can make grammatical sentences. Teaching vocabulary must also be equipped with strategies that are suitable for students. Many strategies can be used by teachers. In vocabulary, there are many things that must be equated and good handling must be taken so that students can understand what vocabulary is. This research was conducted at MTs N 7 Kebumen. The subjects of this study were the English teachers in seventh grade. The purpose of this research is to find the strategies used by English teachers in teaching vocabulary. This research find out students' responses toward the application of teachers' strategies in teaching vocabulary to seventh grade students of MTs N 7 Kebumen. In the interview with an English teacher at MTs N 7 Kebumen, the researcher found out some obstacles experienced by the teacher. One of the obstacle was students have little vocabulary. Therefore the teacher used strategies which easily accepted by students. The teacher also felt not easy to teaching English. This research discusses about analysis the teachers’ strategies in teaching English vocabulary. This research method used descriptive qualitative to describe the strategy of English teachers in teaching vocabulary. The research focused on the strategies of the English teacher in teaching vocabulary in the classroom. The researcher used interview, docummentation, and questionnaire for data collection techniques. First, the researcher interviewed with English teacher. Second, the researcher conducted data analysis using pictures, lesson plans and syllabus as data docummentation. Third, the researcher also gave questionnaires to students in seventh grade MTs N 7 Kebumen using Google Forms. Based on the analysis, the results of the research are three findings that can be taken. First, there are some strategies used by teachers to teach vocabulary, namely presentation, translation, memorization, playing games, reading, pantomime, action, and body movements. Second, this research found out the media used to convey the material, the media used are real things, videos, pictures, English books of students. Third, the researcher found out students' responses with strategies used by the teacher. The researcher concluded that students can enjoy teaching and learning that the teacher gives. By using presentations, translations, memorization, playing games, words, mime, actions, and movements. Students also can remember new words more easily. Keyword: Strategies, Students, Teachers, Teaching, Vocabulary